Inventarisasi Jenis-Jenis Tumbuhan Famili Araceae Dan Marantaceae Di Taman Inklusi Kota Bandung - Hanum Salsabila; Karrisa Zahratul Shaumi; Ateng Supriyatna (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
Inventory is the process of collecting and compiling information and data about natural resources, which can be used as a reference for introducing plant types in the research area. This research was carried out in the Inclusive Park, a park intended for people with special needs, which is also decorated with several types of plants whose types are not yet known. This research aims to determine the types of the Araceae and Marantaceae families that live in the Bandung City Inclusive Park, which has never been done before, so it was deemed necessary to obtain data about this family. The Araceae and Marantaceae families are herbaceous plants that are widely used as ornamental and medicinal plants. The data collection method was carried out directly using an exploratory method and identifying plants at the location using the PlantNet Identification application. The results of the observations obtained 5 types of plants from the Araceae family and 4 types of plants from the Marantaceae family.